Developing and validating a cross-cultural competence scale for Japanese nurses - Masako Sakamoto; Shigemi Iriyama; Yu Mon Saw (PLoS ONE, 2025)
In recent years, Japan has experienced a significant increase in the number of foreign students and workers entering the country. This has resulted in a vast number of international patients in medical facilities. This shift emphasizes the immediate need for Japanese nurses who are both clinically proficient and culturally attuned. In response, our research developed and validated the Cross-cultural Competence Scale for Japanese Nurses (CCCSJN) to better equip nurses for diverse patient care. We conducted a cross-sectional study in Japan’s general hospitals using anonymous questionnaires with nurses and midwives. The scale, developed from data from 394 nurses, underwent both qualitative and quantitative evaluations to define its construct. We analyzed the data using exploratory factor analysis, criterion-related validity, internal consistency, and test-retest reliability, confirming the scale’s reliability and validity. The exploratory analysis revealed five factors: “cross-cultural understanding,” “cross-cultural communication ability,” “motivation for cross-cultural nursing,” “cooperation with multiple professions,” and “respect for foreign patients.” These factors explained 50.92% of the total variance. Cronbach’s α for the CCCSJN was 0.94, and the test-retest reliability correlation was 0.77. The construct validity, criterion-related validity, internal consistency, and test-retest reliability of the CCCSJN were verified. The CCCSJN can be used to assess the cross-cultural competencies of Japanese nurses and identify what skills need to be mastered, leading to improved cross-cultural competence and care.